1991
DOI: 10.1007/bf00769038
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of (Na, K)-ATPase? isoforms in the central nervous system

Abstract: 1. mRNA transcripts for three isoforms of the alpha subunit of (Na,K)-ATPase have been previously identified in the rat nervous system and designated alpha 1, alpha 2 and alpha 3. 2. In order to study the localization and expression of the different alpha isoform mRNAs on a regional and cellular level in the brain, we prepared probes from the unique 3' untranslated region of rat alpha 1 cDNA and from a segment containing a portion of the translated region of rat alpha 3 cDNA. These probes were used in dot blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
64
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 22 publications
(23 reference statements)
13
64
0
1
Order By: Relevance
“…In neurons, the Na ϩ gradient across the plasma membrane varies as a result of activity-dependent transient influx via voltage-and ligand-gated ion channels. Neurons express two ␣ isoforms: ␣1, which is ubiquitous, and ␣3, which has a very restricted expression (4,5). Although disease mutations of ␣3 give rise to serious neurological symptoms such as rapid onset dystonia parkinsonism (6), cognitive deficits (7,8), mood disturbances (9,10), and alternating hemiplegia of childhood (11,12), the relative role of the two ␣ isoforms at the cellular level in neurons is not completely understood.…”
mentioning
confidence: 99%
“…In neurons, the Na ϩ gradient across the plasma membrane varies as a result of activity-dependent transient influx via voltage-and ligand-gated ion channels. Neurons express two ␣ isoforms: ␣1, which is ubiquitous, and ␣3, which has a very restricted expression (4,5). Although disease mutations of ␣3 give rise to serious neurological symptoms such as rapid onset dystonia parkinsonism (6), cognitive deficits (7,8), mood disturbances (9,10), and alternating hemiplegia of childhood (11,12), the relative role of the two ␣ isoforms at the cellular level in neurons is not completely understood.…”
mentioning
confidence: 99%
“…Although there is no detailed knowledge on the isoforms of Na + /K + pump α-subunit in the snail nervous system, based on existing data (Cortas et al, 1989;Blanco and Mercer, 1998), it would be reasonable to assume that snail neurons express different Na + /K + pump α-subunit isoforms that have certain similarities with α-subunit isoforms in mammalian neurons. It has been shown that neurons of mammals express α1 and α3 isoforms of the Na + /K + pump catalytic subunit (Hieber et al, 1991;Watts et al, 1991;Pietrini et al, 1992;Brines and Robbins, 1993). Furthermore, previous research revealed grouping of different types and even subtypes of mammalian neurons based on their Na + /K + pump current density (Dobretsov et al, 1999a;Anderson et al, 2010).…”
Section: Namentioning
confidence: 99%
“…The alpha isoform is the catalytic subunit of the pump [87]. Although the sodium pump is expressed ubiquitously, the α 3 isoform is specifically expressed at high levels in some neurons [88]. Research into the mutations of ATP1A3 causing DYT12 suggest that in this disorder, pumps with the α 3 isoform exhibit decreased stability and hindered function [75].…”
Section: Rapid Onset Dystonia Parkinsonism (Dyt12)mentioning
confidence: 99%
“…Interestingly, and in stark contrast to the basal ganglia, infusion of the cerebellum was sufficient to induce dystonia. The α 3 malfunction was suspected to be especially detrimental for cerebellar function because Purkinje cells, the sole output of the cerebellar cortex express only this isoform [88,95]. At this point, dystonia was characterized by persistent co-contraction of agonist and antagonist muscle pairs quantified using electromyography and the appearance of prolonged abnormal postures rated by observers blinded to the condition of the animal on a dystonia scale.…”
Section: A Pharmacological Model Of Dyt12mentioning
confidence: 99%